(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The present work focuses on formulation of erodible ocular films of valacyclovir hydrochloride (VH) for the treatment of ocular herpes to enhance therapeutic effect through prolonging contact time with the corneal surface. Nine films were prepared by solvent casting method using different ratios of polymers HPMC E 15 LV and PVP. The FT-IR studies showed no interaction between drug and the polymers. Developed formulations were evaluated for tensile strength, % elongation at break, strain, folding endurance, uniformity of thickness, weight variation, % moisture absorption, surface pH, drug content, in vitro release, kinetics study, sterility test and eye irritancy test on Rabbit eye. On the basis of these evaluations it was found that with increase in hydrophilic polymer content the mechanical properties and release rate of the films were improved. The kinetic study revealed case II transport. The eye irritancy test showed that the films were free from ocular toxicity and irritancy. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21866 Dhaka Univ. J. Pharm. Sci. 13(1): 75-81, 2014 (June)